Réponses

2013-04-01T16:02:29+02:00

- 5n(3n + 2)(-6n + 4) = 0

Je reconnais une équation produit. Or un produit est nul si l'un de ses facteurs est nul.

donc

 

-5n = 0

 

OU

3n + 2 = 0

3n + 2 - 2 = 0 - 2

3n / 3 = - 2 / 3

n = -2 / 3

 

OU

-6n + 4 = 0

-6n + 4 - 4 = 0 - 4

- 6n / - 6 = - 4 / - 6 

n = 4/6

 

25a² - 1/4 = 0

25a² - 0,25 + 0,25 = 0 + 0,25

V25a = V0,25

5a / 5= 0,5 / 5

a = 0,01

 

(t + 3)² = 16

t² + 6t + 9 - 9 = 16 - 9

t² + 6t = 7

 

2013-04-01T16:03:48+02:00
( t + 3 ) = 16
t + 3 - 3 = 16 - 3
t = 13

- 5n ( 3n + 2 ) (-6n + 4 ) = 0
Soit a = 0 ou b = 0 ou c = 0

- 5 n = 0
-5n/-5 = 0
N = 0

(3n+2) = 0
3n + 2 - 2 = 0 - 2
3n = -2
3n/3 = -2/3
n = -2/3

-6n + 4 = 0
-6n + 4 - 4 = 0 - 4
6n = -4
6n/6 = -4/6
N = -2/3

Les solutions sont 0 et -2/3